Potencial fisiológico de sementes de soja resfriadas sob diferentes temperaturas - Anjos, Mônica Cristina Rezende dos (2023)
Soybean is considered one of the globally significant crops. In Brazil, it is grown in regions with tropical and subtropical climates that experience high temperatures during the storage period. Therefore, research carried out on the storage process at low temperatures is of fundamental importance to maintain the quality, viability and productivity of soybean seeds. Thus, the present study aims to evaluate the physiological potential of soybean seeds by applying dynamic cooling at different temperatures as a replacement for the aeration process preceding storage. The seeds were submitted to tests to determine moisture content, physical purity, germination, accelerated aging, tetrazolium, dry mass of aboveground and root parts, and emergence in a sand bed. The experimental design was completely randomized in split-plot over time, with treatments consisting of four storage temperatures (12, 15, 18 and 32 ºC – control) evaluated at eight time intervals (0, 7, 14, 21, 28, 35, 42, and 49 days). The outcomes were subjected to analysis of variance at a 5% significance level, followed by the Tukey test for mean comparison. The results obtained in the tests showed superior indices, above the standards, during the early storage periods, but with a decrease in the percentage of vigor, which is related to seed deterioration due to moisture. Consequently, it is concluded that artificially cooled soybean seeds have superior physiological potential compared to non-cooled seeds, especially at temperatures of 12 ºC, which helps maintain longevity, reduces losses in future plantings, and leads to higher yields.